第1章(1)

第1ç«&n...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ° 1 ðØ Øð “Ø ” ð “Ø 2ð ºVÿ ¸ ”* Ø (1)ð Ø i“ ” s Ø ð s (RLC)s Ø (2)ð 3ð Ø Ø Ø ð s s * ª (1)¸ ºVÿ [email protected] 1 ( €X €X €X €X €X €X €X €X s * ª º (V 2ý )È (3) s €X 4s : s 1s s 7s 2.4s 2.5s 4.8s* ª5V.ý8È º [email protected] 2 s > 1¬ ˜Õ * ª º 7 Î 1.1 õØ õØ õØ õØ s tsª º V n˜ *ý s x(t )s x[n]s 1.1.1* ª º V ˜ý * ª º V ý 1˜ (1) Ø x(t ) = e − t x(t ) = sin(ω 0t ) (2) õØ [email protected] 3 s > 1¬ è* ª º 7Õ Î 2 (1)€z s €z €z €z €z x x(t )s €z x s x[n]x [email protected] 4 s > 1¬ h* ª º 7Õ Î u (t ) t = 0 t t∈R u (t ) pc pc x[0] x[1] x[2] pc x pc * ª=V Øü º *ªºV¬ ü (2)p [email protected] 5 s > 1¬ À* ª º 7Õ Î €ø t0 € ø ø €ø t0 €ø (3) x €ø x ∃T > 0s x(t ) = x(t + T )s ∀ts x(t ) = sin(ω 0t )s ø *ªºWΗ Ð t0 x €ø ø ªºWÐ H €ø ∃ N x[n] = x[n + N ] ∀n x[n] = sin(πn 2) [email protected] 6 s > 1¬ Õ * ª º 7 Î (4) p * ª ºV η ü x(t ) = x(−t ) x[n] = x[− n] * ª ºV η ü x(t ) = − x(−t ) x[n] = − x[−n] p ∀x(t ) *xe (º tV )η ªü p x(t ) = xe (t ) + xo (t ) p xo (º tV )η *ª ü 1 xe (t ) = [ x(t ) + x(−t )] 2 1 xo (t ) = [ x(t ) − x(−t )] 2 [email protected] 7 s > 1¬ H* ª º 7Õ Î (5) s x(t )è8 V ö hºª* ( R = 1Ω)s ªºVη ö P(t ) = x(t ) 2 [email protected] 8 s > 1¬ ˜Õ * ª º 7 Î x t2 t2 t1 t1 Et1t2 = ∫ P (t )dt = ∫ x(t ) dt t1 ~ t 2x t1 ~ t 2Ξ * ª üV º Pt1t2 = 2 Et1t2 t 2 − t1 ∞ E = lim Et1t2 = ∫ x(t ) dt s t1 → − ∞ t 2 →∞ 2 −∞ Et1t2 1 t2 2 P = lim = lim ∫t1 x(t ) dt t1 → − t − t ∞ t1 → − t − t ∞ 2 1 1 t →∞ t →∞ 2 ª º ü XV 2 x E < ∞x 0< P <∞ P = 0x 2 x(t )x E→∞ (x x(t ) [email protected] )x ( ) 9 s > 1¬ À* ª º 7Õ Î m ° m ° 1 2 P = ∫ x(t ) dt TT *ªX ºó V 1.1.2ª º V ó X * 1 m ° m ° s ªºVó X 2 (1)¸ò ¸ò [email protected] 10 s > 1¬ @ ª º 7Õ* Î (2) s @ s@ s@ 1. 2 ªh ºó V @ 1.2.1 s@ x(t ) = Ae st 1s A ∈ R s = σ + jω ∈ C ω = 0s x(t ) = Aeσ ts σ >0 σ <0 σ =0 x*(tª )η º óV x*(tª )hóV º x*(tª )η º óV x(tª )η º óV [email protected] 11 s > 1¬ Õ * ª º 7 Î 1 τ= σ 2 σ =0 x(t ) = Ae jω t (1)e jω tH x(t ) ∗ ♠ ≡ ς e jω t cos(ωt ) + j sin(ωt ) 1 jω t cos(ωt ) = ( e + e − jω t ) 2 1 j ω t − jω t sin(ωt ) = (e − e ) 2j [email protected] 12 s > 1¬ Õ * ª º 7 Î (2)e * jωª t hó ºV T = 2π ω ϕ k (t ) = e jkω 0t (* 3ª )hó ºV k =0 k = 0 ±1 ± 2 ϕ 0 (t ) = 1 k = ±1 ϕ ±1 (t ) = e ± jω 0t k = ±2 ϕ ± 2 (t ) = e ± j 2ω 0t 1 ªºVη ó 1 2 ϕ k *(ª tº )η Vó ϕ k (t ) ϕ k (t T0 ) T0 = 2π * ª ωη º V ó0 2 k ≠l ∫ T0 ϕ k (t )ϕ l* (t )dt = 0 k = l [email protected] ∫ T0 ϕ k (t )ϕ l* (t )dt = T0 13 s > 1¬ X* ª º 7Õ Î * ª º V x(t ) T0 ª V º x(tª ) V º ùp ϕ k (t ) x(tª ) V º x(t ) = ∞ ∑a ϕ k =− ∞ 3 σ ≠0 ω ≠0 k k (t ) x(t ) p x(t ) = Ae st = Ae (σ + jω )t = Aeσ t cos(ωt ) + jAeσ t sin(ωt ) [email protected] 14 s > 1¬ À* ª º 7Õ Î 1.2.2 * ª º 18û V 1 t > 0 u (t ) = 0 t < 0 (1)u (t ) (2)8ûºª* V 1 t > t0 u (t − t0 ) = 0 t < t0 [email protected] 15 s > 1¬ Õ * ª º 7 Î (3) u (tª )¨ *ù ºV G (t ) = u (t ) − u (t − t0 ) x(t ) = u (t − 1) − u (t − 2) x(t ) = u (t + 2) − u (t + 1) x(t ) = u (−t − 1) − u (−t − 2) [email protected] 16 s > 1¬ ˜Õ * ª º 7 Î x(t ) = sin( 2πt )u (t ) x(t ) = sin( 2πt )[ u (t − 1) − u (t − 5)] x(t ) = t [ u (t ) − u (t − 2)] + (4 − t )[ u (t − 2) − u (t − 4)] [email protected] 17 s > 1¬ Õ * ª º 7 Î ª (4)˜õ ºV 1 t>0 sgn (t ) = − 1 t < 0 sgn (t ) = u (t ) − u (−t ) sgn (t ) = 2u (t ) − 1 [email protected] 18 ...
View Full Document

Ask a homework question - tutors are online